2011
DOI: 10.1007/s10763-011-9319-7
|View full text |Cite
|
Sign up to set email alerts
|

First- And Second-Generation Immigrant Adolescents’ Multidimensional Mathematics and Science Self-Concepts and Their Achievement in Mathematics and Science

Abstract: This study, drawing on data from the Trends in International Mathematics and Science Study 2007, examined the predictive effects of multiple dimensions of mathematics and science self-concept-positive affect toward mathematics and science and self-perceived competence in mathematics and science-on mathematics and science achievement among 1,752 first-and second-generation immigrant adolescent students in Canada. First-and second-generation immigrant adolescent students' self-perceived competence in mathematics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…Finally, learning style was directly related to motivation and attitude towards mathematics, and motivation directly positively related to attitude towards mathematics. The study of Areepattamannil and Kaur (2012) found out that positive affect towards mathematics influenced in mathematics achievement and, it has a great impact to students' mathematics achievement when teaching strategy coincide with the students' learning style (Tebabal & Kahssay, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, learning style was directly related to motivation and attitude towards mathematics, and motivation directly positively related to attitude towards mathematics. The study of Areepattamannil and Kaur (2012) found out that positive affect towards mathematics influenced in mathematics achievement and, it has a great impact to students' mathematics achievement when teaching strategy coincide with the students' learning style (Tebabal & Kahssay, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Esta investigación propone un modelo institucional para la integración de las minorías que ubica la sucesión generacional de inmigrantes y las cohortes sucesivas de segunda generación integradas en una estructura institucional cambiante. Y analizando la variable educativa Areepattamannil (2012), basándose en datos de Trends in International Mathematics y Science Stydy 2007, examinó los efectos predictivos de múltiples dimensiones de autoconcepto y competencia de matemáticas y ciencias entre 1 752 estudiantes adolescentes inmigrantes de primera y segunda generación en Canadá.…”
Section: La Segunda Generación Como Objeto De Estudiounclassified
“…According to Citizenship and Immigration Canada (2005), immigrant children and youth in the 0-24 age group are the second largest group of permanent residents, accounting for an average of 37.3%. A significant proportion of young immigrants are of school age, and comprise the largest and fastest growing segment of the youth population in Canada (Gluszynski and Dhawan-Biswal, 2008;Areepattamannil, 2011). While most racial minorities in Canada are immigrants, a Canadian-born generation is emerging: by 2001, it constituted 29.4 percent of the racial minority population.…”
Section: Introductionmentioning
confidence: 99%
“…This is a social justice concern and as such the question is not whether the state needs to do something to remedy the problem but rather when and how it will undertake to correct the problem. Given that the percentage of racialized youth will increase due to immigration, and that a sizeable and increasing proportion of young immigrants are of school age (Gluszynski and Dhawan-Biswal, 2008;Areepattamannil, 2011), it should be of great interest to the Canadian government to ensure successful integration of immigrant children in order to secure the growth of national human capital. Therefore, when concerns rise regarding the discrimination of the racialized youth in Canada by the state agents, it becomes a national issue of social equity.…”
Section: Introductionmentioning
confidence: 99%